A base de cálculo das contribuições ao PIS/PASEP e da COFINS e os ônus fiscais: método semiótico - Barros, Matheus Alcântara (2016)
This dissertation involve the analysis of the matter of the inclusion or no inclusion of tax onuses into the base of calculation of the Contributions to the PIS/PASEP and of the COFINS along the chain of normative positivation. It is used here the Semiotics developed by Charles Sanders Peirce aiming to organize the Juridical System, showing it as a chain with signical properties. Thus, the elements of the Positive Law System, or, the legal rulings, are going to be seen as Interpretants, of which types, of the triad Immediate, Dynamical, and Final, will determinate the different stages in which will be discussed the matter related to the mentioned Social Contributions. Therefore, inferences will be made about the Immediate Interpretants which consists of the legal rulings over taxing competency to institute the Contributions to the PIS/PASEP and the COFINS and their Basic-rules, about the Dynamical Interpretants which consists of the legal rulings that constitutes the paying duties of these Contributions, and about the Final Interpretants which consists of the legal rulings produced or to be produced, with the force of the Judged Matter, about the topic. The dissertation aim to, initially, introduce the Logic of the Signs of Peirce, explaining about its premises and about some of its great variation of tools, which will be used at the analysis of the Law, seen in its dependency on the language (on “Signs”, therefore) to manifest itself, to only then specifically face the matter of the inclusion or no inclusion of tax onuses into the base of calculation of the Contributions to the PIS/PASEP and of the COFINS